Analisis Informasi Anatomi antara Sekuens T2WI FSE dan Proton Density Fat Saturation pada Pemeriksaan MRI Knee Joint Potongan Sagital (Studi pada Anterior Cruciate Ligament (ACL) dan Posterior Cruciate Ligament (PCL)) - Atina Izzah Kusumaningrum; Lidya Purna WS Kuntjoro; Gatot Murti Wibowo (Poltekkes Kemenkes Semarang, 2016)
Background: There are clinical situations that radiology physicians need to assess Anterior Cruciate Ligament (ACL) and Posterior Cruciate Ligament (PCL) clearly with the two typical sequences (T2WI FSE sequence and Proton Density Fat Saturation). However, a slight difference in using the applied sequences will result different levels of image quality information. The aim of this study is to compare clinical manifest in anatomical information on the resulted images between T2WI FSE sequence and Proton Density Fat Saturation and to define the best sequence that fit to reveal ACL and PCL of the knee joint..Methods: The research was an experimental quasy. 20 sagital slices of the knee jointMRI were acquired from 10 volunteers who underwent MRI examinations with the two methods (T2WI FSE and Proton Density Fat Saturation). 3 experienced radiology physicians blended in the image scoring when review ACL and PCL appearances on knee MRI images. Inter-observer suitability was checked with Kappa test. A non-parametric Wilcoxon analyses was the statistical tool to test the null hypothesis.Results: The result showed a significant difference in anatomical information of ACL and PCL when T2WI FSE and Proton Density Fat Saturation sequences applied on the MRI of the knee jointsagital slices (p-value 0,05). The mean rank of T2WI FSE was better than Proton Density Fat Saturation which contributed to the value at 4,50. There was an increase in signals that lead to ACL and PCL appear to be more hyper-intens compared to sorrounding organs in general, except the border line of PCL. By this means, it was useful for evaluating the patient whose particularly with ACL post-grafting.Conclusion: There was the difference in anatomical information between T2WI FSE sequence and Proton Density Fat Saturation on MRI knee jointwith sagital slices for ACL and PCL studies. T2WI FSE sequence was the best method for showing anatomical information of ACL and PCL, although a relative low signal still occured from border line of PCL.